KONTRIBUSI KECEPATAN DAN KELINCAHAN TERHADAP KETERAMPILAN DRIBBLING PADA TIM SEPAK BOLA ZALAKKA FC (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the lack of mastery of dribbling techniques by most of the Zalakka FC football team players. The aim of this researchwas to determine the contribution of speed and agility to players' dribbling skills. The population in this researchwas all players of the Zalakka FC football team with a total sampling technique of 20 players. This research examines the contribution of speed and agility to the dribbling ability of players with instruments, namely the 30-meter running test, Illinois agility run and dribbling, with a kind of correlation. Analysis of test requirements using normality test with data analysis techniques using correlation and determination. Based on the results of the study, it can be concluded that there is a 72.76% contribution in speed to dribbling, there is an 85.56% contribution in agility to dribbling and that there is also an 81.18% contribution to speed and agility against dribbling in Zalakka FC footballers.Key Words: Contribution of speed and agility, dribbling skills in football